Selection of Electric Vehicles for Public Use Using AHP - Nader A. B. Al Theeb; Ahmad Eyad Taha; Mohammad Yousef Al Atari (Journal of ICT, Design, Engineering and Technological Science, 2019)
As the entire world shifts from the use of normal vehicles, which consumes fuel, to the use of electric vehicles; this project aims to help the customers choose the best Electric Vehicle (EV) to use for the courier logistics in the Jordanian market, using Analytical Hierarchy Process (AHP). This decision-making methodology, AHP, has been extensively used to make decisions in different logistics branches. The main phases of using this tool in this research are to select the alternatives, which are the EVs, choose appropriate criteria for selection, and construct a realistic comparison matrix based on technical data or experts’ opinions. To apply this methodology, four quantitative criteria and six qualitative criteria for selection were used, βive types of electrical and/or hybrid vehicles are considered because they are available in the Jordanian market, and both technical data and experts’ opinions were used to construct the comparison matrices. It is found in the results that consistency ratios are less than 10%, which means that the data are acceptable. Additionally, it is found that the reliability criterion gets the highest interest among participants who βilled out the survey. Finally, Tesla S is found to be the best choice based on different criteria and its economically feasible to be used.